THE STANDARD C.P.A. EXAMINATION. - Zebley, John H. (The Accounting Review, 1942)
Twenty-five years ago the U.S. Council elected the first Board of Examiners of the American Institute of Accountants. The date exactly was September 20, 1916. At that time the Institute was known as the Institute of Accountants in the United States of America and had just become the successor organization to the American Association of Public Accountants and shortly thereafter the name was changed to American Institute of Accountants. At the outset the purpose of the Board was to conduct examinations into the qualifications of applicants for membership in the Institute and that function it continues to exercise. Accordingly, the first rules and regulations of the Board, which were adopted November 13, 1916, related to requirements for membership in the American Institute of Accountants. Uniformity in examinations for the C.P.A. certificate throughout the nation is today nearer the goal which was envisioned back in 1917 than it has ever before been. The examinations for the C.P.A. certificate in the U.S. states continue to be of high caliber and are comparable with the standard examination used by the 46 State and Territorial Boards as prepared by the American Institute.